Results of robotic liver surgery in association with IWATE criteria - the first 100 cases - Steinkraus, Kira Carlotta; Traub, Benno Konstantin; Heger, Patrick; Zaimi, Marin; Mihaljevic, André Leopold; Michalski, Christoph; Kornmann, Marko; Hüttner, Felix (Langenbeck's archives of surgery, 2024)
Background: Aim of the current study was to present the results of the implementation phase of a robotic liver surgery program and to assess the validity of the IWATE difficulty score in predicting difficulty and postoperative complications in robotic liver surgery. Methods: Based on the prospective database of the Interdisciplinary Robotic Center of Ulm University Hospital, the first 100 robotic liver surgeries were identified and analyzed. Perioperative parameters (duration of surgery and blood loss) and postoperative parameters including morbidity, mortality, and length of hospital stay were assessed and the results were compared between different IWATE difficulty categories. Results: From November 2020 until January 2023, 100 robotic liver surgeries were performed (41 female, 59 male; median age 60.6 years, median BMI 25.9 kg/m2). Median duration of surgery was 180 min (IQR: 128.7), and median blood loss was 300 ml (IQR: 550). Ninety-day mortality was 2%, and overall morbidity was 21%, with major complications occurring in 13% of patients (≥ grade 3 according to Clavien/Dindo). A clinically relevant postoperative biliary leakage was observed in 3 patients. Posthepatectomy liver failure occurred in 7% (4 Grade A, 3 Grade B). Duration of surgery (p < 0.001), blood loss (p < 0.001), CCI (p = 0.004), overall morbidity (p = 0.004), and length of hospital stay (p < 0.001) were significantly increased in the IWATE ‘expert’ category compared to lower categories. Discussion: Robotic surgery offers a minimally invasive approach for liver surgery with favorable clinical outcomes, even in the implementation phase. In the current study the IWATE difficulty score had the ability to predict both difficulty of surgery as well as postoperative outcomes when assessing the complexity of robotic liver surgery. Therefore, the role of the IWATE score in predicting these outcomes highlights its importance as a tool in surgical planning and decision-making.